If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(t + 2) = 28 Reorder the terms: -4(2 + t) = 28 (2 * -4 + t * -4) = 28 (-8 + -4t) = 28 Solving -8 + -4t = 28 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -4t = 28 + 8 Combine like terms: -8 + 8 = 0 0 + -4t = 28 + 8 -4t = 28 + 8 Combine like terms: 28 + 8 = 36 -4t = 36 Divide each side by '-4'. t = -9 Simplifying t = -9
| (4x+10)+8x= | | 4-3/(x^2) | | 4x^2-7x-j=0 | | 3(-2-6)= | | 49-14=5(x-6) | | (2u-5)(6+u)=0 | | x+24+4x=-22-4x-26 | | -1/4x=21/4 | | (15x+7y)+(48x+25y)= | | 7-3(x-1)=2x | | an=-6n+10 | | x+1/2=0.98 | | -16t^2+20t+4=0 | | z/10-4=10 | | -1/X=0 | | a^2+21a-540=0 | | (45x+54y)+(-2x+33y)= | | 4x-2/2=-3 | | -u/12=12 | | -7+|-5|= | | x-0.08x=1700 | | 18+6x-12=-8-4x+9x | | (9x^(1/2))^2 | | 14z-7/7 | | 2*B+3*A=5 | | (14x-27y)+(32x+65y)= | | 5/6x^2*3/6x^2 | | 3(x-4)=12x-4-9x | | 2x^3-15x^2+24x+12=0 | | (50x-8y)+(32x+37y)= | | 24+x=-18 | | -3x^2-12x+1=0 |